FRI0334 COMPARATIVE ASSESSMENT OF COMORBIDITY IN ANKYLOSING SPONDYLITIS, PSORIATIC ARTHRITIS WITH AND WITHOUT SPINAL INVOLVEMENT. (2nd June 2020) - Dadalova, A.; Vasilenko, E.; Samigullina, R.; Mazurov, V.
Abstract : Background: Axial spondyloarthritis (axSpA) is a chronic inflammatory disease is associated with a lot of comorbidities, especially the diseases of cardiovascular system. [1] These diseases not only lead to a decrease in the quality of life and disability of patients, but also to a decrease in life expectancy in comparison with the general population. [2] Objectives: The goal of study is to identify the most significant and common comorbid conditions in patients with axial spondylitis and compare their prevalence in three groups: in patients with ankylosing spondylitis, patients with psoriatic arthritis with and without spinal involvement. Methods: The study included 140 patients with a reliable diagnosis of axSpA (ASAS criteria, 2009), which were subsequently divided into three groups: patients with ankylosing spondylitis, patients with psoriatic arthritis with and without spinal involvement. In all patients comorbid conditions was evaluated. Results: The most common comorbid conditions among patients with axSpA were overweight (65%), included obesity (44%), hypertension (45%), diabetes and prediabetes (31, 4%), dyslipidemia (23, 6%), coronary heart disease (9, 3%), diseases of the gastrointestinal tract (38, 6%). Then we analyzed the prevalence of these comorbid pathologies in three groups. The characteristics of the groups are presented in Table 1 . Conclusion: The prevalence of diseases of the gastrointestinal tract is approximately equal in all three groups, which is probably due to the use of non-steroidal anti-inflammatory drugs and glucocorticoids. The prevalence of the other pathology presented is significantly higher in the groups of psoriatic arthritis and does not significantly differ depending on the involvement of the spine in the pathological process. Due to the high prevalence of cardiovascular disease among patients with psoriatic arthritis, careful monitoring and timely administration of therapy is necessary. References: [1]Zhao SS, et al. Rheumatology (Oxford). 2019 Dec 22. pii: kez573. doi: 10.1093/rheumatology/kez573 [2]Sinnathurai P, et al. Intern Med J. 2018 Nov;48(11):1360-1368. doi: 10.1111/imj.14046. Disclosure of Interests: None declared